2002
DOI: 10.1051/0004-6361:20021399
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of Cu and Zn in metal-poor stars: Clues for Galaxy evolution

Abstract: Abstract. We present new observations of copper and zinc abundances in 90 metal-poor stars, belonging to the metallicity range −3 < [Fe/H] < −0.5. The present study is based on high resolution spectroscopic measurements collected at the Haute Provence Observatoire (R = 42 000, S /N > 100). The trend of Cu and Zn abundances as a function of the metallicity [Fe/H] is discussed and compared to that of other heavy elements beyond iron. We also estimate spatial velocities and galactic orbital parameters for our tar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
194
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(221 citation statements)
references
References 37 publications
26
194
1
Order By: Relevance
“…An inspection of Fig. 6 of Bihain et al (2004) suggests that these measurements substantially agree with those of Mishenina et al (2002), which are essentially based on the measurements of the lines of Mult. 2.…”
Section: Hd 218502supporting
confidence: 59%
See 1 more Smart Citation
“…An inspection of Fig. 6 of Bihain et al (2004) suggests that these measurements substantially agree with those of Mishenina et al (2002), which are essentially based on the measurements of the lines of Mult. 2.…”
Section: Hd 218502supporting
confidence: 59%
“…It was not until the comprehensive study of Sneden et al (1991) that this trend was clearly defined in a robust way, resting on measurements in a large sample of stars. Recent studies of field (Mishenina et al 2002;Bihain et al 2004) and Globular Cluster stars (Shetrone et al 2001(Shetrone et al , 2003Simmerer et al 2003;Yong et al 2005) have confirmed this trend (see Fig. 1 of Bisterzo et al 2004).…”
Section: Introductionmentioning
confidence: 68%
“…Relative abundances of metals do not show strong variations in DLAs, despite significant changes of the absolute metallicity Z. The Fe/Zn ratio is very close to solar in metal-poor stars with metallicities typical of DLA systems (Mishenina et al 2002;Gratton et al 2003;Nissen et al 2004;see discussion in Vladilo 2004). Deviations from the solar ratio are measured in stars with extremely low metallicities.…”
Section: Extinction Versus N Zn In Dla Systemsmentioning
confidence: 85%
“…Gratton et al (2003) and Fulbright (2000). Cu field star data are obtained from Mishenina et al (2002) and Co field star data are taken from Johnson (2002). Interestingly, there is a lack of Co data for globular clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the Fe-group members have roughly solar abundance ratios with two exceptions: copper and manganese. The relative abundance of Cu is known to be exceedingly subsolar in metal-poor field stars (at metallicities [Fe/H]< −2, [Cu/Fe] approaches −1; Sneden et al 1991a, Mishenina et al 2002). An analogous deficiency of Cu in globular cluster stars has recently been reported by Simmerer et al (2003).…”
Section: Introductionmentioning
confidence: 99%